Student’s Difficulty Analysis Through Realistic Mathematics Education Using Batak Toba Cultures - Sinta Dameria Simanjuntak; Imelda Imelda (SAINTIS Publishing, 2018)
This study aims to describe students' difficulties in solving numerical patterns in the context of the Toba Batak ethnic culture after the implementation of the Realistics Mathematic Education Approach in the context of the Toba Batak Tribe Culture. Subjects in this study were students of class VIII Junior High School (SMP) totaling 32 people. The data collection tool used in this study is a test that totals ten questions in the form of a description. This type of research is a qualitative descriptive study. Data collection techniques are carried out by tests, observation, interviews, and documentation. Data analysis techniques were carried out by data reduction, data presentation, and concluding. The results showed that students had difficulty determining the sequence of numbers, determining the configuration of a sequence of numbers, determining the arithmetic series, determining the number of n first arithmetic series terms, determining the first term n row geometry, and determine the number of n first terms of the geometry series. The causal factor is that students are not able to distinguish the general formula concept of a sequence and the concept of configuration patterns from a sequence of numbers, operating error calculations and not understanding integer ranks.